The new chess computer book - Harding, T. D. (Pergamon chess series., 1985)
The New Chess Computer Book is a revised edition of The Chess Computer Book that contains more than 50 percent new material about chess-playing microcomputers. Since the first edition of the book was written there have been large numbers of machines launched, some of which the author has been able to test over a long period. Inevitably there are new chess-playing, microcomputers machines, and updated modules for older ones, coming out all the time, with launch dates for machines in different countries often being different, due to commercial considerations. However, an attempt has been made to discuss in detail every top-of-the-range machine available on the British market.